2018
DOI: 10.3758/s13423-018-1548-0
|View full text |Cite
|
Sign up to set email alerts
|

Gesture as simulated action: Revisiting the framework

Abstract: The Gesture as Simulated Action (GSA) framework was proposed to explain how gestures arise from embodied simulations of the motor and perceptual states that occur during speaking and thinking (Hostetter & Alibali, Psychonomic Bulletin & Review, 15, 495-514, 2008). In this review, we revisit the framework's six main predictions regarding gesture rates, gesture form, and the cognitive cost of inhibiting gesture. We find that the available evidence largely supports the main predictions of the framework. We also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 225 publications
6
115
1
10
Order By: Relevance
“…These data provide further support for embodiment hypotheses based on observations of compatibility effects involving higher cognitive processes and the movement of other body parts (Chen & Bargh, 1999;Zwaan & Madden, 2005;Mahon & Caramazza, 2008;Barsalou, 2010;Meteyard, Cuadrado, Bahrami, & Vigliocco, 2012;Glenberg & Kaschak, 2002;Dominey et al, 2015;Körner et al, 2015). Our results also provide new data on the relationship between gestures and thought (Hostetter & Alibali, 2008;2010;2019;Alibali et al, 2014). In addition, the work presented here allowed us to identify the level at which the sensorimotor simulation mechanism is activated and therefore to distinguish between explicit and implicit embodiment effects.…”
Section: General Discussion and Conclusionsupporting
confidence: 82%
See 2 more Smart Citations
“…These data provide further support for embodiment hypotheses based on observations of compatibility effects involving higher cognitive processes and the movement of other body parts (Chen & Bargh, 1999;Zwaan & Madden, 2005;Mahon & Caramazza, 2008;Barsalou, 2010;Meteyard, Cuadrado, Bahrami, & Vigliocco, 2012;Glenberg & Kaschak, 2002;Dominey et al, 2015;Körner et al, 2015). Our results also provide new data on the relationship between gestures and thought (Hostetter & Alibali, 2008;2010;2019;Alibali et al, 2014). In addition, the work presented here allowed us to identify the level at which the sensorimotor simulation mechanism is activated and therefore to distinguish between explicit and implicit embodiment effects.…”
Section: General Discussion and Conclusionsupporting
confidence: 82%
“…Nonverbal behavior is a very fertile area for research into the relationships between cognition, emotion and sensorimotor mechanisms posited by the embodiment perspective (Krauss, Chen & Gotfexnum, 2000;Goldin-Meadow, 2003;Pouw, De Nooijer, Van Gog, Zwaan & Paas, 2014;Hostetter & Alibali, 2019). Many scholars have shown that both the processing and production of gestures are based on the instantaneous, automatic and unconscious mechanism of sensorimotor simulation (Gallese & Goldman, 1998;Gallese, 2001;Moors & De Houwer, 2006;Hostetter & Alibali, 2008;Shtyrov, Butorina, Nikolaeva & Stroganova, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several theories suggest how and why gestures occur during communication and thinking. Mechanistic theories mostly propose how gestures arise during communication and thinking (e.g., McNeill, 1992 , 2005 ; Hostetter and Alibali, 2008 , 2018 ). Functionalist theories, on the other hand, try to explain why we use gestures and the functions that gestures serve during communication and thinking, both for the speaker and the listener (e.g., Goldin-Meadow et al, 2001 ; Kita and Özyürek, 2003 ; Pouw et al, 2014 ; Cook and Fenn, 2017 ; Kita et al, 2017 ; Novack and Goldin-Meadow, 2017 ).…”
Section: Functions Of Gestures During Communication and Learningmentioning
confidence: 99%
“…Non-redundant or "mismatching" gestures are common when people talk about knowledge that is based in perception or action (Hostetter and Alibali, 2019). People may express their perceptual or action-based knowledge in their gestures, while at the same time expressing some aspects of that knowledge in verbal form.…”
Section: Students' Gestures and Their Role In Teachers' Instructionmentioning
confidence: 99%